2010
DOI: 10.1002/jso.21461
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recurrence and survival following hepatectomy for large hepatocellular carcinoma: A multicenter analysis

Abstract: For patients with HCC larger than 5 cm, tumor-related factors predict outcomes and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…5 Regarding HCCs > 50 mm in the present study, TACE + 3D-HDCRT led to 64% CR, 79% and 42% overall survival rates at one and 3-years (median, 30 months). Some published series reported that surgical resection of HCCs > 50 mm gives 69% and 37% overall survival rates at respectively 1 and 3-years (median, 20 months) 37,38 , thus at least comparable, although with a trends to inferiority, to our TACE + 3D-HDCRT data.…”
Section: Discussionsupporting
confidence: 82%
“…5 Regarding HCCs > 50 mm in the present study, TACE + 3D-HDCRT led to 64% CR, 79% and 42% overall survival rates at one and 3-years (median, 30 months). Some published series reported that surgical resection of HCCs > 50 mm gives 69% and 37% overall survival rates at respectively 1 and 3-years (median, 20 months) 37,38 , thus at least comparable, although with a trends to inferiority, to our TACE + 3D-HDCRT data.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in accordance with previous studies on other solid malignancies that have reported a more favorable prognosis among patients who undergo complete tumor resection. 23,35–39 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of vascular invasion, multifocality of tumors, and tumor size are considered to predict recurrence after hepatic resection for large HCCs (32). However, microvascular invasion and peritumoral satellite nodules o 1 cm in diameter, which are not detectable on preoperative CT or MR imaging, can be identified only by intraoperative ultrasonography or pathology; preoperative prediction of recurrence after hepatic resection, which facilitates the selection of optimal candidates for resection, is challenging (33).…”
Section: Discussionmentioning
confidence: 99%